(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The increasing global prevalence of cesarean sections has led to growing concern about their long-term effects on maternal and fetal health. A previous cesarean section is a known risk factor for complications in subsequent pregnancies, such as uterine rupture, abnormal placentation, placenta previa, placenta accreta spectrum, preterm birthand adverse perinatal outcomes. These risks pose significant challenges for obstetric care and decision-making regarding the mode of delivery. Investigating the impact of prior cesarean deliveries is essential to guide clinical practices and improve maternal and fetal outcomes in future pregnancies.This study aims to evaluate the maternal and fetal outcomes in women with subsequent CS with a history of previous CS. Materials and methods: This was a prospective observational study of patients who had a previous caesarean section for either maternal or fetal indications. The study lasted for 6 months, from September 2024 to February 2025. A totalof 116 patients were included in this study based on predefined inclusion and exclusion criteria. The indications and maternal and neonatal outcomes were studied. Results: A total of 116 patients were included in this study. The most common age group of the studied cases was 25-29 years (38%). The mean age of the patients was found to be 27.50±4.40 years. One of the most important indications for C-sections was failure to progress (45%), followed by fetal distress 39%, 9% due to contracted pelvis, and 4% due to Cephalopelvic disproportion. with 3% due to malpresentation. The most common complications during subsequent pregnancy were preterm labour 15 (35.71%), following pre-eclampsia 12 (28.57%) and placenta previa 9 (21.43%). Current study showed 72% of babies following CS were admitted in the NICU due to birth asphyxia for low birth weight and 28% due to neonatal jaundice. 92% of fetuseswere found healthy in the cases studied, whereas only 8% suffered from developmental delay. Conclusions: The study highlights that previous cesarean sections significantly impact both maternal and fetal outcomes in subsequent pregnancies. Complications such as preterm labor, pre-eclampsia, and placenta previa were notably frequent. Neonatal outcomes also reflected increased risk, with a high NICU admission rate primarily due to birth asphyxia and low birth weight. Despite these challenges, the majority of fetuses (92%) remained healthy, underscoring the importance of vigilant prenatal care in pregnancies following a cesarean delivery. JCMCTA 2025 ; 36 (1) : 147-153